Review of the Cenozoic Floras and Vegetation of Greece (Review of Palaeobotany and Palynology)
Oligocene to Pleistocene floras of Greece are reviewed based on published and unpublished material. Oldest plant-bearing sediments of Rupelian-Chattian age are exposed in eastern Thrace (Evros) and were deposited after the closure of the Turgai Seaway. They contain a blend of (i) taxa that migrated to western Eurasia from the East (Alnus, Fagus), (ii) characteristic Oligocene taxa (Nyssa altenburgensis, Ampelopsis hibschii), and (iii) extinct (Eotrigonobalanus, Quasisequoia) and modern genera (Calocedrus, Quercus Group Lobatae) from older epochs. Coastal palm swamps and laurel forests of the hinterland indicate a subtropical, fully humid to winter-dry climate (Cfa, Cwa according to Köppen). The Aquitanian-Burdigalian plant assemblage of Lesbos is intermediary between Evros and the Burdigalian floras of Euboea sharing taxa with Evros (palms), and with Euboea and early Miocene floras of Anatolia (Güvem, Tilia). In the early Miocene (Burdigalian) floras of Euboea, species of Quercus Group Ilex (Q. drymeja, Q. mediterranea) characteristic of fully humid or winter-dry (monsoon) climates (Cf, Cw) became dominant elements in well-drained forests. Floristic links are with late Oligocene to middle Miocene floras of Central Asia (Tilia), Asia Minor (cycads, Quercus Group Ilex, Tilia), and South and Central Europe (cycads, Quercus Group Ilex, palms). Middle Miocene floras are restricted to the Aegean islands (Chios). Biogeographic links are with early to late Miocene floras of Central Europe (Parrotia, Podocarpium) and with middle Miocene floras of Anatolia (Parrotia). Upper Miocene plant-bearing sedimentary formations are most abundant in Greece and exposed on the Ionian Islands, Greece mainland to East Macedonia, Peloponnese, Aegean Islands, and Crete. Overall, the fossil plant assemblages from Greece mainland are indicative of fully humid conditions during this time (Cfa), with Fagus and oaks of Quercus Group Ilex being dominant elements. Seasonality may have been more pronounced on the Peloponnese and the Aegaean Islands and Crete, expressed by the rare occurrence of Fagus in the fossil records of these areas. The palaeobotanical records from Samos unambiguously point to the presence of forest vegetation during early Tortonian to Messinian (Cwa) when the famous vertebrate faunas of Samos were deposited. The Pliocene is characterized by the regional occurrence of modern types of deciduous oaks mainly of Quercus Group Cerris and Quercus subsect. Galliferae. East Asian links persist in Fagus, Quercus, and Cupressaceae, North American ones in Sabal; several other mesophytic taxa from previous periods are recorded as well. The modern sclerophyllous Mediterranean vegetation, thriving in a warm summer dry climate (Csa), cannot be traced prior to the Pleistocene based on the palaeobotanical record.